2011
DOI: 10.3109/08916934.2010.541170
|View full text |Cite
|
Sign up to set email alerts
|

Nephritogenic antibodies bind in glomeruli through interaction with exposed chromatin fragments and not with renal cross-reactive antigens

Abstract: Cross-reactivity of anti-double stranded DNA (anti-dsDNA) antibodies with glomerular antigens has been postulated as a key factor in the development of lupus nephritis. Because no direct proof has been presented on anti-dsDNA antibodies binding in vivo to glomerular structures, we have analysed the binding of potentially nephritogenic anti-dsDNA antibodies to α-actinin and laminin. By enzyme-linked immunosorbent assay and surface plasmon resonance (SPR) analyses, we demonstrate that monoclonal antibodies (mAbs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
37
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 49 publications
0
37
1
1
Order By: Relevance
“…An example of such cross-reactivity is antidsDNA antibodies in SLE, which have been shown to recognize antigens in the glomerular basement membrane, where these autoantibodies can deposit (44)(45)(46)(47). While the binding of some anti-dsDNA antibodies to glomeruli depends on the presence of nucleosomes containing DNA on the glomerular membrane, the contribution of cross-reactivity to renal pathology has also been demonstrated (48,49).…”
Section: Tlr Recognition and Its Role In Escape From Tolerancementioning
confidence: 99%
“…An example of such cross-reactivity is antidsDNA antibodies in SLE, which have been shown to recognize antigens in the glomerular basement membrane, where these autoantibodies can deposit (44)(45)(46)(47). While the binding of some anti-dsDNA antibodies to glomeruli depends on the presence of nucleosomes containing DNA on the glomerular membrane, the contribution of cross-reactivity to renal pathology has also been demonstrated (48,49).…”
Section: Tlr Recognition and Its Role In Escape From Tolerancementioning
confidence: 99%
“…12,[16][17][18][19][20] Chromatin and nucleosomes deriving from ineffective fragmentation may interact with negatively charged constituents of the basement membrane 7,16 and become the planted antigen for anti-dsDNA (and autoantibodies of other specificities). 6,7,9,16 Other potentially nephritogenic antibodies different from anti-dsDNA have been proposed 10,11,[21][22][23][24][25][26] ; overall, it has been estimated that anti-DNA deposition in LN accounts for not more than 10%-20% of eluted IgG overall, 27 implying that IgG not recognizing DNA represents the vast majority of antibodies in glomeruli. Renal targets of autoimmunity in human LN are, however, unknown.…”
mentioning
confidence: 99%
“…[6][7][8][9][10][11][12] They consider a pre-eminent role of circulating anti-double stranded DNA (dsDNA) antibodies that they can interact, for mimicry, with glomerular antigens expressed at the cell surface of podocytes and mesangial cells 7,[13][14][15] or in the glomerular basement membrane. 12,[16][17][18][19][20] Chromatin and nucleosomes deriving from ineffective fragmentation may interact with negatively charged constituents of the basement membrane 7,16 and become the planted antigen for anti-dsDNA (and autoantibodies of other specificities).…”
mentioning
confidence: 99%
“…6 Three categories of autoantibodies have been identified that constitute the basis for any pathologic and clinical consideration. The first category targets implanted antigens (DNA, histones, and nucleosomes), [7][8][9][10] mainly deriving from breakdown of apopotic cells. The second category of antibodies binds C1q, which is a component of the complement cascade accumulating in the kidney in LN.…”
mentioning
confidence: 99%